Naked Metal Cations Swimming in Protein Crystals - Kristina Djinović-Carugo; Oliviero Carugo (Crystals, 2019)
The presence of isolated metal cations, far from any other atom, is not uncommon in protein crystal structures. A systematic survey of the Protein Data Bank showed that nearly 8% of the metal cations are naked, more frequently if they can interact only electrostatically with their neighbors. Surprisingly, this seemed to be only weakly related to the crystallographic resolution.